Dharmaṭhākura, Śūnyapurāṇa prasaṅge - Rāmāi Paṇḍita,Bandyopādhyāẏa, Bı̄reśvara (Lokasaṃskr̥ti o Ādibāsī Saṃskr̥ti Kendra, Tathya o Saṃskr̥ti Bibhāga, Paścimabaṅga Sarakāra, 2017)
Poetry on Dharmaṭhākura, Hindu deity worshiped by villagers in the traditional Rarh region, West Bengal.
Enthält Literaturangaben
Keywords: Dharmaṭhākura; Poetry.; Bengali poetry.